Potential Use of Coal Bottom Ash as Fine Aggregate Replacement: A Review - ABDUL HALIM, WANN SHARFRINA; SARIF, ABD SUKOR (Progress in Engineering Application and Technology, 2021)
The most common pavement used in the Malaysian roadway is flexible pavement which is a mixture of asphalt and bitumen. Bitumen is used as a binder to bind the aggregates, fillers, and binders which is used for road building and repair is asphalt. Asphalt sustainability could be increased by replacing the aggregates with waste material such as coal bottom ash. Coal bottom ash produced from coal combustion is used to replace fine aggregate in asphalt pavement mixture and compare with a standard mixture. Due to the increasing quantity of coal combustion waste, there is needed to search for another alternative way to reduce the residues by recycling the coal bottom ash. This study aims to investigate the Marshall properties of the asphalt mixture and determine the optimum percentage of bottom ash by comparing data from the previous study. Lab tests that are used in this project are the Marshall Stability Test. All researchers using optimum of bottom ash (6%-25%) which resulting the Marshall stability ranges from 11.17kN to 22.00kN. Accordingly, it is comply with the JKR Standard value which is higher than 8kN. From this study, the cost to dispose of the ash will be reduced and the sustainability of the environment will be maintained, hence improving the engineering properties of asphalt.